Combined Geometric and Neural Network Approach to Generic Fault Diagnosis in Satellite Actuators and Sensors. Issue 17 (2016) - Baldi, P.; Blanke, M.; Castaldi, P.; Mimmo, N.; Simani, S.
Abstract: This paper presents a novel scheme for diagnosis of faults affecting the sensors measuring the satellite attitude, body angular velocity and flywheel spin rates as well as defects related to the control torques provided by satellite reaction wheels. A nonlinear geometric design is used to avoid that aerodynamic disturbance torques have unwanted influence on the residuals exploited for fault detection and isolation. Radial basis function neural networks are used to obtain fault estimation filters that do not need a priori information about the fault internal models. Simulation results are based on a detailed nonlinear satellite model with embedded disturbance description. The results document the efficacy of the proposed diagnosis scheme.